Notes on Early Land Plants Today. 73. Genera of Lejeuneaceae established in the period 1884–1893: dates of validation and implications - Söderström, Lars; Barrie, Fred; Hagborg, Anders; Crandall-Stotler, Barbara; Gradstein, Robbert; Stotler, Raymond E.; Konrat, Matt Von (Phytotaxa, 2015)
Dates of validation of generic names initially published as names in subgenera or sections of Lejeunea (mainly by Spruce) in the period 1884–1893 are established. Consequences for the dates of validations of specific names are analysed. Names not validly published (both generic and specific names) in this period are also identified. A few species names must be changed from those in common use today and two new combinations, Rectolejeunea versifolia and Lejeunea hyalina, become necessary.